No gain without pain: using pain tracking mobile Apps - Chaudhry, Beenish M. (mHealth, 2016)
Chronic pain often remains untreated because tracking its causes and symptoms is difficult. By recording details of pain episodes, retrospectively analyzing data around pain and sharing it with experts, pain management can be demystified and better treatment options can be suggested.